Game-based learning to enhance motivation and fundamental motor skills in elementary physical education: a quasi-experimental study - Dese, Dennys Christovel; Wibowo, Cahyo; Widyaningtyas, Rut; Nopiyanto, Yahya Eko (Edu Sportivo: Indonesian Journal of Physical Education, 2025)
Background: Game-based learning (GBL) is widely used in physical education to enhance student motivation and fundamental motor skills (FMS). However, evidence from elementary school contexts, particularly using quasi-experimental designs with intact classes, remains limited.  Objectives: This study examined the effects of a 12-week game-based learning intervention on motivation and fundamental motor skills among elementary school students. Methods: A quasi-experimental one-group pretest–posttest design was employed involving 34 elementary school students selected through purposive sampling. The 12-week intervention consisted of weekly 105-minute sessions of dexterity-based game learning. Motivation was measured using a validated questionnaire, while fundamental motor skills were assessed through an age-appropriate motor skills test. Data were analyzed using descriptive statistics, normality and homogeneity tests, and paired-sample t-tests, with Cohen’s d calculated to estimate effect size. Finding/Results: The experimental group demonstrated significant increases in motivation and FMS from the pre-test to the post-test (p < 0.05). Although the effect size was small to medium, the observed increases reflect short-term positive changes following the intervention. Conclusion: The 12-week GBL intervention effectively enhanced motivation and FMS among elementary school students. While the findings support the use of GBL in physical education, the absence of a control group and potential class-level confounders limit causal interpretation. Future studies should employ randomized or controlled designs and include broader measures of engagement and motor competence.